Audit culture, accountability, and care: A phenomenological anthropology of child welfare. (November 2021) - Valenzuela, Robin
Front-line child welfare workers have long since preoccupied social work, sociological, and anthropological scholarship. This article employs phenomenological anthropology to attend to the embodied, experiential, and sensorial dimensions of front-line child welfare work. However, rather than renew calls to improve casework through increased institutional support, resilience-building, or retention efforts, I draw on caseworkers' lived experiences to engage in a critical examination of the state's role as parens patriae. What do caseworkers' experiences "on the inside" reveal about the state's capacity to care—both for its own frontline staff and the families in its purview? How do such experiences problematize our understanding of state accountability? Ultimately, how can they shift the scholarly fixation on developing "better" workers who can accommodate the ever-increasing demands of casework, to a larger critique of the state's ability to serve as "the guardian and ultimate guarantor of child welfare" (Boyden, 2005 : 195)? By locating caseworkers' experiences within a larger context of "audit culture"—a climate of suspicion and surveillance that forces workers to constantly account for their productivity and performance—this article problematizes the state's model of accountability and care (Shore and Wright, 2000 ). I argue that, in light of the toxic social dynamics it creates, "audit culture" is incommensurable with the state's role as parens patriae.